Minocycline reduces microgliosis and improves subcortical white matter function in a model of cerebral vascular disease. Issue 1 (19th July 2017) - Manso, Yasmina; Holland, Philip R.; Kitamura, Akihiro; Szymkowiak, Stefan; Duncombe, Jessica; Hennessy, Edel; Searcy, James L.; Marangoni, Martina; Randall, Andrew D.; Brown, Jon T.; McColl, Barry W.; Horsburgh, Karen
Abstract: Chronic cerebral hypoperfusion is a key mechanism associated with white matter disruption in cerebral vascular disease and dementia. In a mouse model relevant to studying cerebral vascular disease, we have previously shown that cerebral hypoperfusion disrupts axon‐glial integrity and the distribution of key paranodal and internodal proteins in subcortical myelinated axons. This disruption of myelinated axons is accompanied by increased microglia and cognitive decline. The aim of the present study was to investigate whether hypoperfusion impairs the functional integrity of white matter, its relation with axon‐glial integrity and microglial number, and whether by targeting microglia these effects can be improved. We show that in response to increasing durations of hypoperfusion, the conduction velocity of myelinated fibres in the corpus callosum is progressively reduced and that paranodal and internodal axon‐glial integrity is disrupted. The number of microglial cells increases in response to hypoperfusion and correlates with disrupted paranodal and internodal integrity and reduced conduction velocities. Further minocycline, a proposed anti‐inflammatory and microglia inhibitor, restores white matter function related to a reduction in the number of microglia. The study suggests that microglial activation contributes to the structural and functional alterations of myelinated axons induced by cerebral hypoperfusion and that dampening microglia numbers/proliferation should be further investigated as potential therapeutic benefit in cerebral vascular disease. Main Points: Cerebral hypoperfusion impairs the functional integrity of white matter which is significantly associated with axon‐glial integrity and microglia proliferation. Minocycline dampens microgliosis restoring white matter function.